An Overview of Drug-Related Criminal Acts as Extraordinary Crimes in Indonesia - Husni; Muhammad Nur (International Journal of Law, Social Science, and Humanities, 2024)
Indonesia is a nation that has unfortunately become a target for drug trafficking, resulting in a growing number of drug-related crimes each year. To address drug crime in Indonesia, the government has issued Law No. 35 of 2009 on Narcotics and Law No. 5 of 1997 on Psychotropic. The Indonesian government's efforts to eradicate drugs crime have not been successful. This study employs a qualitative research design with a normative approach. Our study revealed that law enforcement has been considereed optimal due to the government's establishment of the National Narcotics Agency (BNN) as a specialized, independent institution with broader authority than other law enforcement agencies. The 2009 Narcotics Law, specifically Law No. 35, establishes strict penalties for drug abuse, which can include imprisonment, additional punishment, or even the death penalty